2016
DOI: 10.1037/pri0000027
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in exposure therapy for PTSD treatment.

Abstract: Continuous improvement of clinical care and outcomes is always the goal of medical science. Within posttraumatic stress disorder (PTSD) treatment, innovations may focus on improving access and overcoming barriers to effective interventions as well as improving efficacy. Innovations may include entirely novel interventions, augmentation of new strategies to known effective interventions, or modification of known effective interventions to increase retention, speed of response, or overall impact. Exciting work o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…However, these modifications have not resulted in clinically significant improvement of either outcome or dropout rates. A relatively new strategy is to deliver the treatment sessions in a highly intensive format (Hendriks, de Kleine, Hendriks, & van Minnen, 2016; Rauch & Rothbaum, 2016), with patients attending multiple sessions within a compact period of time (e.g. within one week) instead of weekly sessions over the course of several months.…”
Section: Introductionmentioning
confidence: 99%
“…However, these modifications have not resulted in clinically significant improvement of either outcome or dropout rates. A relatively new strategy is to deliver the treatment sessions in a highly intensive format (Hendriks, de Kleine, Hendriks, & van Minnen, 2016; Rauch & Rothbaum, 2016), with patients attending multiple sessions within a compact period of time (e.g. within one week) instead of weekly sessions over the course of several months.…”
Section: Introductionmentioning
confidence: 99%
“…A single case study combining EMDR and ERP with antidepressant treatment had low results on several measures ( Nijdam et al, 2013 ). Rauch and Rothbaum (2016) suggested that ERP and exposure-based therapies could be considered for PTSD for individuals who do not wish to participate in evidence-based treatments. ERP was not endorsed by the APA ( Bufka et al, 2020 ) and VA/ DoD (2017) guidelines ( not recommended at this time ).…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical applications of VR in the field of counseling occur in the context of treatment with disabilities and self‐esteem (Nosek et al., 2016), childhood and adolescent social anxiety (Sarver et al., 2014), nightmares (McNamara et al., 2018), posttraumatic stress disorder (Rauch & Rothbaum, 2016), and so forth. This technology has yet to be used as a frontline training tool in counselor education.…”
Section: Experiential Learning and Counselor Educationmentioning
confidence: 99%